ONLINE AND DIGITAL COMMUNICATION PRACTICES DURING THE CORONAVIRUS PANDEMIC: THE CASE OF PUBLISHING HOUSES IN MACEDONIA - Koneska-Vasilevska, Tea (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2023)
Summary: The subject of our research is online and digital communication practices during the coronavirus pandemic on the part of publishing houses in Macedonia. Certain aspects of the research subject include changes in communication and interaction between publishing houses and the readership, as well as the use of social networks. The research started from the main research question: "What were the online and digital communication practices of publishing houses in Macedonia during the coronavirus pandemic?" The main goal of the research is: to identify the online and digital communication practices of publishing houses. Qualitative methodological techniques, semi-structured interview and qualitative content analysis, were used. The research is based on the fact that in times of global crisis, communication technologies and culture could be transformed into instruments of social change, for the benefit of the individual and humanity, and as a "helping tool" for dealing with certain consequences, creating new, improved conditions for life, action and creation of new forms of communication and interaction and exchange and creation of cultural content. From the conducted interviews and content analysis, we can conclude that during the pandemic, especially during the period of quarantine and curfew in 2020, most of the communication between publishing houses and the readership was transmitted online. What is key to the change in communication and interaction between them is that activities and events that are usually carried out with physical presence, "live", in the pandemic period were carried out online, so that the whole way of organizing those activities and events changed, and thus habits and the use of certain Internet and digital technologies and tools have also changed.